2022
DOI: 10.1111/den.14295
|View full text |Cite
|
Sign up to set email alerts
|

Clinical outcomes following endoscopic or video‐assisted retroperitoneal management of acute pancreatitis with large (>15 cm) walled‐off pancreatic necrosis: Retrospective, single tertiary center cohort study

Abstract: Objective Acute pancreatitis with walled‐off necrosis (WON) is associated with considerable morbidity and mortality. Previous studies have evaluated outcomes in WON collections of limited size, while data about large WON with long‐term follow‐up are lacking. We aimed to report our experience in managing large WON. Methods Between 2010 and 2020, consecutive patients with large (>15 cm) WON were identified from a prospectively maintained database. Patients with chronic pancreatitis or an index intervention 90 da… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 36 publications
0
15
0
Order By: Relevance
“…Our treatment algorithm included a scheduled weekly dilatation of the drainage tract for patients in the DPT group, which may not be the standard practice. However, it is our experience that in patients with large WON, endoscopic dilatation is required to counteract spontaneous closure of the tract and to avoid retention in WON with the subsequent risk of systemic infection 3 23. Obviously, this resulted in there being more endoscopic procedures carried out in the DPT group than in the LAMS group.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our treatment algorithm included a scheduled weekly dilatation of the drainage tract for patients in the DPT group, which may not be the standard practice. However, it is our experience that in patients with large WON, endoscopic dilatation is required to counteract spontaneous closure of the tract and to avoid retention in WON with the subsequent risk of systemic infection 3 23. Obviously, this resulted in there being more endoscopic procedures carried out in the DPT group than in the LAMS group.…”
Section: Discussionmentioning
confidence: 99%
“…In general, mortality among patients with infected WON is estimated to be 10%–20%. Our group recently presented retrospective data from patients with WON exceeding 15 cm in diameter and found an in-hospital mortality of 17% 23. These data come from consecutive patients referred for treatment at our tertiary care unit between 2010 and 2020.…”
Section: Discussionmentioning
confidence: 99%
“…A recent study found no difference between 10, 15 and 20 mm LAMS for PFC [ 47 ]. Another study also indicated that endoscopic drainage of WON patients is effective and less invasive than surgery [ 48 ].…”
Section: Discussionmentioning
confidence: 99%
“…Methods Nine patients with infected WON not amenable for EUS guided transgastric drainage or VARD were retrospectively enrolled 1 2 3 .…”
mentioning
confidence: 99%